A6.9 Directed Transport of microRNAs from Apoptotic Cells to Phagocytes by Membrane-Coated Vesicles (MCVs). (25th February 2013) - Claßen, L; Tykocinski, LO; Wiedmann, F; Krienke, S; Lauffer, A; Heyder, P; Blank, N; Schiller, M; Lorenz, HM
Abstract : Background and Objectives: A distinctive feature of cell activation and apoptotic cell death is the formation of MCVs. MCVs have previously been identified as mediators of cell-to-cell communication and are recognised as carriers of microRNA. An impaired clearance of apoptotic debris has been observed in SLE patients. This is caused by an increased rate of apoptosis and by a defect in phagocytic-cell clearance. We investigated differences in the microRNA content of MCVs released by activated and apoptotic lymphoblasts from normal healthy donors (NHDs) and SLE patients. MicroRNA content of lymphoblasts and MCVs and the effect of MCV uptake into monocytes were analysed. Materials and Methods: Activated lymphoblasts, UV-B irradiated lymphoblasts and corresponding MCVs of NHDs and SLE patients were compared in an Agilent microRNA array and validated by qPCR MiR-155 expression was determined by qPCR in monocytes with engulfed autologous UV-MCVs. Western blot was performed to investigate the expression of the miR-155 target protein Tab-2. Results: MiR-155, miR-155*, miR-34b and miR-99a were significantly less expressed in UV-lymphoblasts compared to non-irradiated lymphoblasts. The effect was even more pronounced in staurosporine-treated lymphoblasts. In contrast, the expression of miR-34a increased after UV-B irradiation but decreased under staurosporine treatment. The comparison of viable and apoptotic MCVs showed a decrease of miR-155* in apoptotic MCVs. In UV-MCVs, the miR-99a level was higher compared to viable MCVs. MiR-155 was not altered in MCVs after apoptosis induction. MiR-34a was expressed at higher levels in viable SLE lymphoblasts and MCVs compared to NHDs. In contrast, miR-34b expression was decreased in UV-lymphoblasts and UV-MCVs of SLE patients. In functional assays we could demonstrate higher miR-155 levels and consecutively decreased target protein levels in monocytes after engulfment of autologous UV-MCVs. Conclusions: Our data show an unequal distribution of the content of different microRNAs within apoptotic cells and cell derived MCV. This suggests a directional transport rather than a random distribution. Thus, cells can regulate their microRNA as well as the microRNA content within released MCV. We could show that microRNA and protein expression changes in phagocytes after UV-MCV engulfment. Thus, our results suggest that MCVs could serve as a transport vehicle for microRNAs to mediate cell-cell communication and influence intracellular processes in the phagocyte. Disturbances of this system could contribute to the pathogenesis of SLE.